2018
DOI: 10.2147/ijn.s161908
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced endosomal escape by photothermal activation for improved small interfering RNA delivery and antitumor effect

Abstract: BackgroundEffective endosomal escape is still a critical bottleneck for intracellular delivery of small interfering RNAs (siRNAs) to maximize their therapeutic efficacy. To overcome this obstacle, we have developed a photothermally triggered system by using the near-infrared (NIR) irradiation to achieve “on-demand” endosomal escape and subsequent siRNA release into cytoplasm.Materials and methodsHerein, the poly-L-lysine (PLL) was successfully conjugated with melanin to obtain melanin-poly-L-lysine (M-PLL) pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…The achieved siRNA-mediated low-temperature PTT was able to completely suppress tumor growth upon laser irradiation in HeLa tumor-bearing mice model, as a result of the cooperative enhancement of the efficacy of PTT by GT. In a similar way, Yang et al demonstrated the activity of a melanin-poly-l-lysine (M-PLL) polymer as a siRNA vehicle, able to the overcome the endosomal barrier and to deliver into the cytoplasm the functional genetic material [202]. M-PLL nanoparticles exhibited good biocompatibility, biodegradability and siRNA electrostatic-binding capacity with an optimal ratio of 40:1 M-PLL/siRNA.…”
Section: Ptt-gene Therapymentioning
confidence: 95%
“…The achieved siRNA-mediated low-temperature PTT was able to completely suppress tumor growth upon laser irradiation in HeLa tumor-bearing mice model, as a result of the cooperative enhancement of the efficacy of PTT by GT. In a similar way, Yang et al demonstrated the activity of a melanin-poly-l-lysine (M-PLL) polymer as a siRNA vehicle, able to the overcome the endosomal barrier and to deliver into the cytoplasm the functional genetic material [202]. M-PLL nanoparticles exhibited good biocompatibility, biodegradability and siRNA electrostatic-binding capacity with an optimal ratio of 40:1 M-PLL/siRNA.…”
Section: Ptt-gene Therapymentioning
confidence: 95%
“…It has been reported that photothermal activation can be employed to enhance endosomal escape of therapeutic cargos. 47,48 As shown in Figure 2, Au 800 -CTAB-PAA-PEG-AA exhibited a SPR in response to the wavelength of 800 nm. When stimulated with laser irradiation at 808 nm, 2.5 W/cm 2 for 0.5 minutes, the surface temperature of Au 800 -CTAB-PAA-PEG-AA and Au 800 -CTAB-PAA-PEG-AA.EPI was increased to ~55°C and ~65°C, respectively ( Figure S5), and such temperature is sufficient for hyperthermal effect.…”
Section: Formulation and Physicochemical Characterization Of Aunrepimentioning
confidence: 95%
“…This localization suggests that NPs appear to work in lysosomes, but in some situations, the function of the lysosomes might decrease NP efficacy. For example, some studies have used NPs to deliver siRNA into cancer cells for gene therapy, but the siRNA might be digested in lysosomes [216]. To overcome this problem, several strategies for facilitating endosome escape, such as ion pair formation, the "proton sponge effect", destabilization of the endosome membrane, and the hydrophobic modification of the NPs, have been researched [217].…”
Section: Issues Of Integrin-targeted Npsmentioning
confidence: 99%